Sustained-release salt reservoir enables durable solid electrolyte interphases for practical micron-sized silicon composite anodes - Kui Lin; Junke Wu; Zhengguang Song; Yuling Yi; Fuxi Peng; Shiwen Wang; Zhimin Zou; Tongbin Lan; Junxiong Wu; Chunhai Jiang (Chemical Engineering Journal, 2026)

Suitable particle-size biochar enhances resilience of potato production and soil environmental to irregular precipitation in semiarid region - Zhaoyang Li; Nan Shi; Zhimin Yang; Yubo Cao; Shimeng Fan; Musawer Abbas; Weixing Shan; Ansabayeva Assiya; Zhikuan Jia; Enke Liu; Kadambot H.M. Siddique; Ruixia Ding; et al. (Bioresource Technology, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Antibacterial mechanisms of terpinen-4-ol against Aeromonas hydrophila - Kaiqi Lian; Xiangfeng Meng; Yuhang Wang; Shengming Ma; Xiaolong Li; Ren Ren; Yuling Liu; Lingling Zhou; Renhai Peng (Archives of Microbiology, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Deep fertilization effects on potato production and GHG emissions depend on soil C:N:P-enzyme interactions: Evidence from a 4-year study - Zhaoyang Li; Nan Shi; Yixuan Yuan; Haiyang Chang; Yuling Meng; Weixing Shan; Moskvicheva Elena; Ansabayeva Assiya; Zhikuan Jia; Xiaolong Ren; Kadambot H.M. Siddique; Ruixia Ding; et al. (European Journal of Agronomy, 2026)

Adjusting fertilization depth for sustainable potato production in arid and semi-arid regions - Zhaoyang Li; Yukang Wang; Nan Shi; Yixuan Yuan; Lianjun Wei; Weixing Shan; Medelbek Meruyert; Ansabayeva Assiya; Zhikuan Jia; Kadambot H.M. Siddique; Ruixia Ding; Peng Wu; et al. (Field Crops Research, 2026)

Multistimuli-responsive degradable metal-organic framework nanoplatform potentiates photoimmunotherapy for hepatocellular carcinoma via cGAS-STING pathway activation - Yahui Wu; Zhipu Liu; Yi Zhang; Senfeng Zhao; Miaoqing Li; Ruiyang Zhang; Jiahui Cao; Peng Liu; Liming Song; Yin Liu; Yunpeng Zhai; Weijie Wang; et al. (Chemical Engineering Journal, 2026)

Interpretable machine learning model based on floc images for monitoring the coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Peng Guo; Chuanchuan Dou; Wangben Zhao (Process Safety and Environmental Protection, 2026)

Recent heat wave across the Yunnan-Guizhou plateau and its impact on alpine lakes - Jiabin Peng; Junxu Chen; Xiaohui Pan; Yuling Luo; Siqi Feng; Tie Liu; Xi Chen (Journal of Cleaner Production, 2026)

Utilizing phosphogypsum-derived CaAl LDH-chitosan to remove Pb2+ from oil/gas field wastewater: Adsorption behavior and competitive mechanism - Jing Bai; Qijia You; Yushuan Peng; Zhihao Li; Yuling Zhang; Qiulin Deng; Huiwei Liao; Faqin Dong; Xiaofeng Zeng; Zixun Yan (Process Safety and Environmental Protection, 2025)

Synthesis of guanylhydrazone functionalized tetraphenylethylene for combating antibiotic resistance and biofilms - Shuwen Guo; Zijun Chen; Yuling He; Haipeng Xu; Yuwei Zhao; Ye Yang; Peng Yang (Chemical Engineering Journal, 2025)

Genome-wide identification and functional analysis of the polyamine metabolism-related genes in Foxtail millet (Setaria Italica L.) - Liuan Hao; Tao Wang; Yangyang Wei; Pengtao Li; Yuling Liu; Quanwei Lu; Huawen Zou; Renhai Peng (Functional & Integrative Genomics, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Genome-wide identification and functional analysis of TCX gene family and the critical role of GhTCX17 in response to drought and salt stress in cotton - Yangyang Wei; Jingjing Zhai; Shuaikang Geng; Shaoliang Zhang; Yongqing Zhao; Bingkai Cui; Huiyun Shan; Yanhua Li; Cong Wang; Pengtao Li; Yuling Liu; Quanwei Lu; et al. (Functional & Integrative Genomics, 2025)

Identification of the STY13 gene family across the entire genome and an analysis of the essential function of GhSTY13-12 in cotton’s response to abiotic stress - Shaoliang Zhang; Huiyun Shan; Xiaopei Bo; Jiahui Li; Zili Liu; Pengtao Li; Yuling Liu; Xiaojie Yang; Quanwei Lu; Sumei Wan; Renhai Peng; Yangyang Wei; et al. (Functional & Integrative Genomics, 2025)

Study on the spatio-temporal variation and trade-off/synergy relationship of ecosystem service value in Western Hubei based on dynamic equivalent method - Weiying Cheng; Yuan Li; Yuling Peng (Environment, Development and Sustainability, 2025)

Genome-Wide Identification of the DVR Gene Family and Expression Analysis of GDF8 Genes in Qihe Gibel Carp - Jinyan Shan; Yuling Liu; Kaiqi Lian; Xianghui Xiao; Jun Ma; Ren Ren; Xiaolong Li; Guoqiang Wei; Youyi Kuang; Renhai Peng (Fishes, 2025)
(1) Background: The BMP/GDF (Bone Morphogenetic Protein/Growth Differentiation Factor) subfamily (Decapentaplegic-Vg1-related, DVR) within the transforming growth factor beta (TGF-β) superfamily plays critical roles in governing biological developmental processes and physiological functions. (2) Methods: In this study, we systematically investigated the DVR gene family in hexaploid Qihe gibel carp (Carassius gibelio var. Qihe) through comprehensive genomic identification, phylogenetic analysis, chromosome mapping, and cis-regulatory element prediction. The experimental design for gene expression analysis involved collecting samples from multiple tissues (brain, muscle, liver, kidney, etc.) and different developmental stages (20, 45, and 60 days post hatching, dph) to examine the expression patterns of four GDF8 genes using quantitative real-time PCR (qRT-PCR). (3) Results: We identified 50 DVR members in Qihe gibel carp. Phylogenetic analysis classified the 50 DVR family members into 20 distinct protein types, with 29 BMPs (Bone Morphogenetic Proteins) and 21 GDFs (Growth Differentiation Factors) identified. All 50 DVR proteins of Qihe gibel carp have similar TGF-β domains except for four BMP1 proteins. Chromosomal localization revealed widespread distribution of DVR members across 36 chromosomes, a pattern potentially linked to the hexaploid genome of Qihe gibel carp. Genes within the same subgroup exhibited conserved intron–exon architectures and similar intron numbers; syntenic conservation within subgroups may reflect functional constraints after polyploidization, implying evolutionary pressure to maintain functional domains. Through spatiotemporal expression profiling, we uncovered functional divergence among four GDF8 (myostatin) paralogs: GDF8-1 and GDF8-2 were predominantly expressed in brain and muscle tissues (dorsal and caudal), while GDF8-3 and GDF8-4 showed hepatic, cerebral, and renal specificity. Intriguingly, all paralogs exhibited a gradual upregulation during late development (20–60 days post hatching, dph), with peak expression staggered between 45 dph (GDF8-1/2) and 60 dph (GDF8-3/4). (4) Conclusions: These findings suggest that GDF8 plays a critical regulatory role in the growth and development of Qihe gibel carp. Collectively, these results provide a foundation for further investigations into the functional roles of the DVR gene family during the ontogenetic development of this species.

Target-activated DNAzyme and ion-functionalized DNA nanospheres enable dual cfDNA homogeneous electrochemical analysis for tuberculosis diagnosis - Yanming Meng; Runlian Qu; Yue Wang; Chunying Zhang; Wu Peng; Yuling Xiao; Hongxia Ruan; Hao Chen; Binwu Ying; Piaopiao Chen (Chemical Engineering Journal, 2025)

Enhanced short-term prediction of urban PM2.5 concentrations by improved hybrid deep learning - Yin Zhou; Yaping Lyu; Xiuli Dang; Roland Bol; Peng Zhang; Na Yu; Yuling Zhang (Journal of Environmental Health Science and Engineering, 2025)

Effect of Limosilactobacillus fermentum NCU001464 fermentation on physicochemical properties, xanthine oxidase inhibitory activity and flavor profile of Pueraria Lobata - Siyun Huang; Xin Yin; Yuling Fang; Tao Xiong; Fei Peng (Food Chemistry, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Impact of white matter hyperintensity location on outcome in acute ischemic stroke patients: a lesion-symptom mapping study - Yuling Peng; Dan Luo; Peng Zeng; Bang Zeng; Yayun Xiang; Dan Wang; Ying Chai; Yongmei Li; Xiaoya Chen; Tianyou Luo (Brain Imaging and Behavior, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

The identification of signature genes and their relationship with immune cell infiltration in age-related macular degeneration - Jinquan Chen; Long Zhao; Longbin Zhang; Yiling Luo; Yuling Jiang; Peng H (Molecular Biology Reports, 2024)

N, S, Se-Codoped dual carbon encapsulation and Se substitution in pyrite-type FeS2 for high-rate and long-life sodium-ion batteries - Yuling Shi; Peng Mei; Tingting He; Chengjiang Deng; Haocun Ba; Junping Hu; Shaozhuan Huang (Chemical Engineering Journal, 2024)

Neutral pH photoenzymatic activity of Au-doped g-C3N4 nanosheet for colorimetric detection of total antioxidant capacity in food samples - Xianming Li; Wentong Fan; Honghu Tang; Dongdong Li; Yuling Xiao; Bin Yang; Yi Zhao; Peng Wu (Food Chemistry, 2024)

Site-directed immobilization of enzymes on nanoparticles using self-assembly systems - Haili Zhou; Yuling Fang; Jing Zhang; Tao Xiong; Fei Peng (Bioresource Technology, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Genomic, Physiological, Biochemical, and Phenotypic Evidences Reveal a New Species, Halomicroarcula salaria sp. nov - Tao Hong; Juntao Ke; Liangzhon Chen; Yuling Hao; Peng Lu; Shaoxing Chen (Current Microbiology, 2024)

Smartphone-based electrochemical sensor for cost-effective, rapid and on site detection of chlorogenic acid in herbs using biomass-derived hierarchically porous carbon synthesized by a soft-hard dual template method - Wanjun Jiang; Zhonghui Zhuo; Xiaohua Zhang; Hai Luo; Lu He; Yuling Yang; Yangping Wen; Zhong Huang; Peng Wang (Food Chemistry, 2024)

Wheat adaptation to environmental stresses under climate change: Molecular basis and genetic improvement - Hude Mao; Cong Jiang; Chunlei Tang; Xiaojun Nie; Linying Du; Yuling Liu; Peng Cheng; Yunfeng Wu; Huiquan Liu; Zhensheng Kang; Xiaojie Wang (Molecular Plant, 2023)

Straw removal or non-removal affects cadmium (Cd) accumulation in soil–rice (Oryza sativa L.) system at different ambient air Cd levels - Si Luo; Yuling Liu; Bihao Luo; Yihao Yang; Li Li; Xin Fu; Liang Peng; Qingru Zeng (Journal of Environmental Management, 2023)

Intergenerational effects of parental [Cnmim]BF4 (n = 4, 6, 8) ionic liquids exposure on zebrafish development based on transcriptomic analysis - Yue Liu; Yanan Tian; Chenning Zhang; Xin Lu; Yuling Xue; Xinping Wang; Qiuyue Liao; Xin Li; Kai Lian; Jiaolong Huang; Jie Deng; Peng Duan (Science of The Total Environment, 2023)

V-ATPase V0 subunit activation mediates maduramicin-induced methuosis through blocking endolysosomal trafficking in vitro and in vivo - Yuling Zheng; Jing Xiao; Junqi Wang; Bin Dong; Dawei Guo; Hui Ji; Haifeng Sun; Lin Peng; Shanxiang Jiang; Xiuge Gao (Food and Chemical Toxicology, 2023)

Variation of Cd and As accumulation in crops under oilseed rape–rice rotation system in response to different contaminated rice straw-return methods - Yuling Liu; Haowei Zeng; Hanglv Zhou; Shijing Zhang; Baiqing Tie; Liang Peng; Qingru Zeng; Hua Peng; Si Luo (Plant and Soil, 2023)

Microbubbles preparation by partial vaporization of low boiling condensate for crude oil/water separation - Ce Wang; Yuling Lü; Chao Song; Jiakai Shi; Peng Zhang; Limin He (Journal of Water Process Engineering, 2023)

Promotional role of Co on Cu-SAPO-34 towards enhanced denitration performance and SO2 tolerance - Yuling Zheng; Yangyang Mi; Yonglong Li; Wenming Liu; Daishe Wu; Yingying Zhang; Zhenguo Li; Honggen Peng (Fuel, 2023)

Effects of a novel plant growth regulator B2 on stalk quality and grain yield of winter wheat in North China - Chuanxi Peng; Yuling Guo; Guanmin Huang; Yingru Liu; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Plant and Soil, 2023)

Remediation of atrazine-contaminated soil in a fluidized-bed DBD plasma reactor - Nan Jiang; Ying Qu; Jinwei Zhu; Hongchang Wang; Ju Li; Yun Shu; Yutao Cui; Yuling Tan; Bangfa Peng; Jie Li (Chemical Engineering Journal, 2023)

Inhibition mechanisms of urea combined with nitrification on cadmium uptake by rice (Oryza sativa L.) seedlings - Li Li; Yuling Liu; Shijing Zhang; Siduo Ding; Xin Fu; Qingru Zeng; Liang Peng; Si Luo (Plant and Soil, 2023)

Large-scale metabolome analysis reveals dynamic changes of metabolites during foxtail millet grain filling - Tao Wang; Lu Xing; Hui Song; Yangyang Wei; Pengtao Li; Quanwei Lu; Nan Hu; Yuling Liu; Yongqing Zhao; Jinrong Liu; Baohong Zhang; Renhai Peng (Food Research International, 2023)

Estimating the prevalence of hypertension in 164 cities in China by wastewater-based epidemiology - Chenzhi Hou; Yuling Zhong; Lan Zhang; Muyuan Liu; Fang Yan; Mengyi Chen; Youmei Wang; Peng Xu; Mengxiang Su; Chi Hu; Bin Di (Journal of Hazardous Materials, 2023)

Novel sensor array distinguishes heavy metal ions based on multiple fluorescence channels from dendritic mesoporous silica nanoparticles - Xiaotong Wu; Lei Tan; Yuling Li; Wanqiong Liu; Zhihua Peng; Yanshan Dong; Zeyu Huang; Lin Zhang; Yong Liang (Analytica Chimica Acta, 2023)

Toxicity of ceria nanoparticles to the regeneration of freshwater planarian Dugesia japonica: The role of biotransformation - Changjian Xie; Xiaowei Li; Lisha Hei; Yiqing Chen; Yuling Dong; Shujing Zhang; Shan Ma; Jianing Xu; Qiuxiang Pang; Iseult Lynch; Zhiling Guo; Peng Zhang (Science of The Total Environment, 2023)

Achieving highly efficient near-ultraviolet emitters via optimizing molecular configuration by the intramolecular-locked donor and acceptor - Daokun Zhong; Xiaolong Yang; Xuming Deng; Xi Chen; Yuling Sun; Peng Tao; Zikang Li; Jie Zhang; Guijiang Zhou; Wai-Yeung Wong (Chemical Engineering Journal, 2023)

Preparation of Functionalized Graphene Oxide Composite Spheres and Removal of Cu2+ and Pb2+ from Wastewater - Huining Zhang; Xingmao Liu; Lihong Tian; Yuling Tang; Zhongyu Shi; Yankui Xiao; Zhiguo Wu; Ying Zhu; Qi Guo; Zhangpu Peng (Water, Air, & Soil Pollution, 2022)

Spatiotemporally varied extreme precipitation events simultaneously controlled by multiple circulation factors in China's Loess Plateau - Yuling Ren; Jingpeng Zhang; Jinxia Fu; Shouzhang Peng; Zhi Li (International Journal of Climatology, 2022)
The intensive and frequent extreme precipitation events (EPE) greatly contribute to the severe soil loss in China's Loess Plateau, and it is thus essential to understand how and why EPE varies with space and time. Particularly, the combined influence of multiple factors on EPE has rarely been explored. This study analysed the spatiotemporal variability of EPE for 1961–2017 after defining six indices for intensity, frequency, and duration of EPE (R5d, SDII, R90t, R90n, CDD, CWD). We employed 12 atmospheric circulation factors to determine their combined effects on EPE on different time scales over time by the multiple wavelet coherence. The EPE indices spatially varied with obvious southeast‐northwest gradients. Averaged across the whole plateau, SDII, R90t, and R90n increased insignificantly, while R5d, CDD, and CWD decreased insignificantly. In addition, the change trend had spatial variations with most wet EPE indices increasing in the north and the southernmost areas and decreasing in the middle‐south areas. SDII, R90t, and R90n at 68%, 66%, and 53% of stations tended to increase, respectively, and R5d, CDD, and CWD decreased at 66%, 70%, and 77% of stations, respectively. The temperature had a greater correlation with the duration of EPE in summer and on the intensity and frequency of EPE in winter. El Niño‐Southern Oscillation (ENSO), Pacific North American teleconnection pattern (PNA), ENSO‐Arctic Oscillation (AO), and ENSO‐AO‐PNA were found to be the main factors influencing EPE individually or simultaneously. This study provides technical support for the identification of combined effects of multiple factors, and the results are helpful for regional environmental management. Specific to the Loess Plateau, the identified individual or multiple factors can be used to project future changes in EPE, and the more frequent and intensive EPE in some regions may increase the difficulty in future soil loss control.

Activation of cadmium under simulated solar illumination and its impact on the mobility of Cd in flooded soils - Bihao Luo; Chenfeng Xiao; Yuling Liu; Li Li; Liang Peng; Qingru Zeng; Si Luo (Environmental Science and Pollution Research, 2022)

Human umbilical cord-derived mesenchymal stem cells ameliorate psoriasis-like dermatitis by suppressing IL-17-producing γδ T cells - Youdong Chen; Yifan Hu; Xue Zhou; Zihan Zhao; Qian Yu; Zeyu Chen; Yuanyuan Wang; Peng Xu; Zengyang Yu; Chunyuan Guo; Xilin Zhang; Yuling Shi (Cell and Tissue Research, 2022)

Travel Behaviours of Sharing Bicycles in the Central Urban Area Based on Geographically Weighted Regression: The Case of Guangzhou, China - Zongcai Wei; Feng Zhen; Haitong Mo; Shuqing Wei; Danli Peng; Yuling Zhang (Chinese Geographical Science, 2021)

Effects of iron, calcium, and organic matter on phosphorus behavior in fluvo-aquic soil: farmland investigation and aging experiments - Yuling Ma; Jie Ma; Hao Peng; Liping Weng; Yali Chen; Yongtao Li (Journal of Soils and Sediments, 2019)

Effects of deficit irrigation combined with rainwater harvesting planting system on the water use efficiency and maize (Zea mays L.) yield in a semiarid area - Peng Zhang; Ting Wei; Yuling Li; Yan Zhang; Tie Cai; Xiaolong Ren; Qingfang Han; Zhikuan Jia (Irrigation Science, 2019)

Connecting gastrointestinal cancer risk to cadmium and lead exposure in the Chaoshan population of Southeast China - Xueqiong Lin; Lin Peng; Xijin Xu; Yanrong Chen; Yuling Zhang; Xia Huo (Environmental Science and Pollution Research, 2018)

Determination of seven pyrethroid pesticide residues in vegetables by gas chromatography using carboxylated multi-walled carbon nanotubes as dispersion solid phase extraction sorbent - Peng Sun; Yuling Gao; Chong Xu; Yongfu Lian (Food Additives & Contaminants: Part A, 2017)

A Highly Selective and Sensitive Fluorescent Turn-on Probe for Al3+ Based on Naphthalimide Schiff Base - Hongping Peng; Kesheng Shen; Shanshan Mao; Xinkui Shi; Yuling Xu; Stephen Opeyemi Aderinto; Huilu Wu (Journal of Fluorescence, 2017)

A highly Selective Fluorescent Sensor for Monitoring Cu2+ Ion: Synthesis, Characterization and Photophysical Properties - Stephen Opeyemi Aderinto; Yuling Xu; Hongping Peng; Fei Wang; Huilu Wu; Xuyang Fan (Journal of Fluorescence, 2017)

Association between blood erythrocyte lead concentrations and hemoglobin levels in preschool children - Chunhua Liu; Xia Huo; Peng Lin; Yuling Zhang; Weiqiu Li; Xijin Xu (Environmental Science and Pollution Research, 2015)

Synthesis, Crystal Structures and Photo- and Electro-Luminescence of Copper(I) Complexes Containing Electron-Transporting Diaryl-1,3,4-Oxadiazole - Tianzhi Yu; Peng Liu; Haifang Chai; Jundan Kang; Yuling Zhao; Hui Zhang; Duowang Fan (Journal of Fluorescence, 2014)

Synthesis, Crystal Structure and Photoluminescence of a Cyclometalated Iridium(III) Coumarin Complex - Tianzhi Yu; Chengcheng Zhang; Yuling Zhao; ShaoQiang Guo; Peng Liu; Wentao Li; Duowang Fan (Journal of Fluorescence, 2013)